(untitled) - Marco Puleri (Studi Slavistici, 2014)
The author analyses the narrative strategies adopted by Emmanuel Carrère in his critically acclaimed work Limonov. Since the different critical approaches, focusing on the definition of a hybrid auto-biographical genre, it is stressed the connection between the autobiographical techniques adopted in his works by Edward Limonov and their influence on Carrère’s ‘portrait’. In Limonov we can observe the dialogue between the narrator and his hero, which represents a moment of reflection on the narrative relationship between reality and fiction in the auto-biographical genre. The author presents the specific devices adopted by the given authors, in order to show their complementary relationship in the process of literary ‘construction of the self ’.